PEMILIHAN MATERIAL RING PADA ILLIZAROV RING EXTERNAL FIXATION - Erwin, Erwin (Mesin, 2016)
Fracture fixation in the bone require a stable, so that the bones in the recovery period did not experience an excessive burden and changing positions, for it takes a fixation device. This fixation device consists of two types that are planted within or outside the body. To keep bones and weight-bearing position, needed a material that has properties of a lightweight rustproof, and have stiffness. This study used a method developed by Asbhy and M. Farag in selecting materials to suit the required operating conditions, and a relatively cheap price. Candidate material composed of Aluminum alloy (Al 2014), 304 Stainless steel, Brass, Titanium alloy (Ti 6AL4V). Beryllium. Selected materials meet the figure of merit is Beryllium.Key Word : Bone fracture, fixation, material selection